2018
DOI: 10.1038/s41366-018-0221-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent blood–brain barrier tracing shows intact leptin transport in obese mice

Abstract: Background/objectivesIndividuals carrying loss-of-function gene mutations for the adipocyte hormone leptin are morbidly obese, but respond favorably to replacement therapy. Recombinant leptin is however largely ineffective for the vast majority of obese individuals due to leptin resistance. One theory underlying leptin resistance is impaired leptin transport across the blood–brain-barrier (BBB). Here, we aim to gain new insights into the mechanisms of leptin BBB transport, and its role in leptin resistance.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 43 publications
0
54
1
2
Order By: Relevance
“…However, Harrison et al used fluorescent BBB tracing and found that although diet-induced obesity (DIO) mice are resistant to leptin, their mediobasalhypothalami (MBH) or ventricular septal organ do not show any defects in leptin accumulation, while LepRa expression in the choroid plexus drives leptin transfer from the blood to the cerebrospinal fluid and its biodistribution in the brain. The difference between these and previous results might stem from the facts that the latter measurement was performed when the accumulation of leptin reached the maximum value of the MBH, and that the authors did not evaluate the ratio of leptin entering the brain relative to the circulation [30]. Nonetheless, these findings provide new starting points for us to explore the mechanisms underlying leptin resistance, so that future research can shift from investigations of the transport of leptin across the BBB to the search for other possible causes of leptin resistance.…”
Section: Leptin and Leptin Resistancecontrasting
confidence: 62%
“…However, Harrison et al used fluorescent BBB tracing and found that although diet-induced obesity (DIO) mice are resistant to leptin, their mediobasalhypothalami (MBH) or ventricular septal organ do not show any defects in leptin accumulation, while LepRa expression in the choroid plexus drives leptin transfer from the blood to the cerebrospinal fluid and its biodistribution in the brain. The difference between these and previous results might stem from the facts that the latter measurement was performed when the accumulation of leptin reached the maximum value of the MBH, and that the authors did not evaluate the ratio of leptin entering the brain relative to the circulation [30]. Nonetheless, these findings provide new starting points for us to explore the mechanisms underlying leptin resistance, so that future research can shift from investigations of the transport of leptin across the BBB to the search for other possible causes of leptin resistance.…”
Section: Leptin and Leptin Resistancecontrasting
confidence: 62%
“…This negative feedback loop was strongly supported by the discovery of leptin (Zhang et al, 1994), genetic mutations in the leptin gene and the MC4R family (Farooqi et al, 1999;Farooqi and O'Rahilly 2008) and the description of leptin resistance in diet-induced obese mice and obese humans (Maffei et al, 1995;Schwartz et al, 1996;Halaas et al, 1997;Friedman 2016). However, in this past decade several studies questioned the existence of leptin resistance (Ottaway et al, 2015;Harrison et al, 2018;Pan and Myers Jr, 2018). Moreover, leptin infusion studies in mice revealed that hyperleptinemia is unlikely to define an obese body weight set point (Ravussin et al, 2014).…”
Section: The Set-point Theory Postulates An Obesogenic Memory Againstmentioning
confidence: 99%
“…Central administration of leptin to obese animals reduces food intake more potently than peripheral administration of the hormone, suggesting that leptin transport to the brain is impaired in obesity (Halaas et al 1997, Van Heek et al 1997. Interestingly, leptin transport across the blood-cerebrospinal fluid barrier (Kleinert et al 2018), rather than across the blood-brain barrier (Harrison et al 2018), seems to be impaired in obese animals. Notably, rats lacking functional LepRa display decreased transport of leptin to the brain and develop obesity (Kastin et al 1999).…”
Section: Brain Accessibilitymentioning
confidence: 99%